Pengaruh Kebiasaan Buruk (Bad Habits) Terhadap Kualitas Hidup yang Terkait Dengan Kesehatan Gigi dan Mulut pada Anak Usia Prasekolah di TK Aisyiyah Gonilan Kartasura - Iqbal, Muhammad, Dwi Kurniawati, S.KG, MPH, drg. Suyadi (2015)
Based on the research in Indonesia and overseas, the prevalence of bad habits of preschool student was very high. The onset of bad habits in children can lead to a disturbance of physical maturation, psychological and pruductivity disturbance that can be seen clearly the form of reduced quality of life. Therefore, the research on the burden and the impact of bad habits is needed, not only the information of prevalence, badness, and medical treatment, but also the impact toward life quality. Aim : This research is aimed to discover the impact of bad habits towardoral health related quality of life preschool students of Aisyiyah kindergarten Gonilan Kartasura. Method : The design of this research is cross sectional that measure risk factor and impact factor at the same time. Non Ramdom sampling was conducted with Quota Sampling method. To identify the bad habits, structured interview was conducted with clinical checkand life quality measurement using Early Childhood Oral Health Impact Scale (ECOHIS). The parents were invited to schoolto fulfill the questionnaire. From the 120 students, there were 62 students have bad habits, 37 have one bad habits, and 25 students have more than one bad habits. The data were analyzed using Mann-Whitney method to know its influence by comparing the result of life quality among the students who have one bad habit and who have more than one bad habits. Result : The result of Mann-Whitney test shows that there are differences score of life quality among the children's group who have one Bad Habit with the children who have more bad habits. Statistically it has a significant result. The result is p=0,000. Conclusion : This research concludes that bad habits influence to the life quality, where the life quality of group who has one bad habit is better than the other group who has more than one bad habit